LEGAL STATUS OF FARMER ENTERPRISES AND THE PROCEDURE FOR THEIR STATE REGISTRATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the legal status of farmer enterprises and the procedure for their state registration under the legislation of the Republic of Uzbekistan. It analyzes the requirements for founding documents, the legal process of registration, and the implications of acquiring legal entity status. The article also addresses practical challenges and offers recommendations for improving legal regulation in the agricultural sector.